Does Expertise Reduce Rates of Inattentional Blindness? A Meta-Analysis. (February 2022) - Ekelund, Malin; Fernsund, Hanna; Karlsson, Simon; Mac Giolla, Erik
Inattentional blindness occurs when one fails to notice a fully visible stimulus because one's attention is on another task. Researchers have suggested that expertise at this other task should reduce rates of inattentional blindness. However, research on the topic has produced mixed findings. To gain clarity on the issue, we meta-analyzed the extant studies ( K  = 14; N  = 1153). On average, experts showed only a slight reduction in rates of inattentional blindness: 62% of novices experienced inattentional blindness compared to 56% of experts, weighted odds ratio = 1.33, 95% CI [0.78, 2.28]. The relevance of the stimuli to the experts' domain of expertise showed no notable moderating effects. The low number of the included studies, and the small sample sizes of the original studies, weaken our conclusions. Nonetheless, when taken together, the available evidence provides little support for any reliable influence of expertise on rates of inattentional blindness.